Constraining the Fluid History of a CO2‐H2S Reservoir: Insights From Stable Isotopes, REE, and Fluid Inclusion Microthermometry. (16th January 2019) - Zwahlen, Carmen; Hollis, Cathy; Lawson, Michael; Becker, Stephen P.; Boyce, Adrian; Zhou, Zheng; Holland, Greg
Abstract: Reservoirs that host CO2 ‐H2 S‐bearing gases provide a key insight into crustal redox reactions such as thermochemical sulfate reduction (TSR). Despite this, there remains a poor understanding of the extent, duration, and the factors limiting this process on a reservoir scale. Here we show how a combination of petrography, fluid inclusion, rare earth element (REE), and carbon (δ 13 C), oxygen (δ 18 O), and sulfur (δ 34 S) stable isotope data can disentangle the fluid history of the world's largest CO2 accumulation, the LaBarge Field in Wyoming, USA. The carbonate‐hosted LaBarge Field was charged with oil around 80 Ma ago, which together with nodular anhydrite represent the reactants for TSR. The nodules exhibit two distinct trends of evolution in δ 13 C with both δ 34 S and δ 18 O that may be coupled to two different processes. The first trend was interpreted to reflect the coupled dissolution of anhydrite and reduction to elemental sulfur and the oxidation of organic compounds and associated precipitation of calcite during TSR. In contrast, the second trend was interpreted to be the result of the hydrothermal CO2 influx after the cessation of TSR. In addition, mass balance calculations were performed to estimate an approximate TSR reaction duration of 80 ka and to identify the availability of organic compounds as the limiting factor of the TSR process. Such an approach provides a tool for the prediction of TSR occurrence elsewhere and advancing our understanding of crustal fluid interactions. Key Points: Sulfate sulfur and oxygen isotopes cofractionated during thermochemical sulfate reduction process The approximate length of TSR is 80 ka A combination of petrography, REE, fluid inclusion, and stable isotope measurements can be useful to disentangle the fluid history of a large CO2 reservoir